Post-exercise recovery of contractile function and endurance in humans and mice is accelerated by heating and slowed by cooling skeletal muscle - Cheng, A. J.; Willis, S. J.; Zinner, C.; Chaillou, T.; Ivarsson, N.; Ørtenblad, N.; Lanner, J. T.; Holmberg, H. C.; Westerblad, H. (The Journal of Physiology, 2017)
Manipulation of muscle temperature is believed to improve post-exercise recovery, with cooling being especially popular among athletes. However, it is unclear whether such temperature manipulations actually have positive effects. Accordingly, we studied the effect of muscle temperature on the acute recovery of force and fatigue resistance after endurance exercise. One hour of moderate-intensity arm cycling exercise in humans was followed by two hours recovery in which the upper arms were either heated to 38°C, not treated (33°C), or cooled to ~15°C. Fatigue resistance after the recovery period was assessed by performing 3 × 5 min sessions of all-out arm cycling at physiological temperature for all conditions (i.e. not heated or cooled). Power output during the all-out exercise was better maintained when muscles were heated during recovery, whereas cooling had the opposite effect. Mechanisms underlying the temperature-dependent effect on recovery were tested in mouse intact single muscle fibres, which were exposed to ~12 min of glycogen-depleting fatiguing stimulation (350 ms tetani given at 10 s interval until force decreased to 30% of the starting force). Fibres were subsequently exposed to the same fatiguing stimulation protocol after 1-2 h of recovery at 16-36°C. Recovery of submaximal force (30 Hz), the tetanic myoplasmic free [Ca2+] (measured with the fluorescent indicator indo-1), and fatigue resistance were all impaired by cooling (16-26°C) and improved by heating (36°C). In addition, glycogen resynthesis was faster at 36°C than 26°C in whole FDB muscles. We conclude that recovery from exhaustive endurance exercise is accelerated by raising and slowed by lowering muscle temperature.